The AIV method for achieving effective comprehension of poetic texts: Experimental study involving application of the AIV method among higher education students - Farje Cuchillo, José Armando (2020)
The purpose of this study was to determine whether or not application of the AIV method (analysis, interpretation and assessment) improves the effective reading comprehension of poetic texts among students at Universidad Privada del Norte. The research applied was of an explanatory, quasitransversal, hypothetical, deductive and quantitative nature. The sample was composed of 45 students for the experimental group (GE) and 46 students for the control group (GC). The same content was taught to both groups, with the AIV method applied to the GE group, while the GC group worked with the standard methodology. The result indicated that the grades achieved by the GE group were higher than those of the GC group. Consequently, a null hypothesis was rejected, and it was concluded that there were significant differences in the reading comprehension of poetic texts in the GE group before and after application of the AIV method.